Collaboration for logistics education in Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)
The era of information and communication technology has triggered the rapid advancement of the logistics industry which leads to strict global competition in distribution of goods and services in the 21st century.